(untitled) (GIST – Education and Learning Research Journal, 2013)
This article deals with parental involvement as a strategy to assist young learners in their efforts to learn an L2. It discusses an 18-month experience involving ten young learners, their parents, and teachers, in the development of another language (L2). The parents had expressed that they were unable to support their children’s development in L2 because they “did not know English.” Classroom observations, analysis of class work, and interviews motivated the authors to pursue this inquiry. The pedagogical innovation consisted of educating parents in what it means to learn an L2, and in training them and their children to tackle assignments. A website was also developed to support this endeavor. The results suggest a positive change in the home environment as a place to learn with parental engagement. The data from this study suggest that training the parents not only facilitated children’s L2 study but contributed to their literacy development as well. The evidence also indicates that the quality of communication between children and parents, the organization of assignments, as well as the quality of written expression improved. When assisting one’s child to learn an L2, fun is as important as it is in learning to ride a bike.